شبكة العلمية العلاقة العلمية العلماء الجاوين والدولة العثمانية في القرن السادس عشر الميلادي إلى القرن الثامن عشر الميلادي - Ulin Nuha (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2022)
Abstract For approximately five centuries, starting from 1571 and actually ending in 1924, the Ottoman Empire controlled the scientific centers in the Hejaz City. During that time, Ulama Jawi enjoyed the golden age of science. Thoriq Aziz, in his book entitled